Antenas e superfícies seletivas de freqüência reconfiguráveis para sistemas de comunicação sem fio - Costa, Iradilson Ferreira da (2009)
This work aims to present how the reconfigurable microstrip antennas and frequency selective surfaces can be used to operate at communication systems that require changing their operation frequency according to system requirements or environmental conditions. The main purpose is to present a reconfigurable circular microstrip antenna using a parasitic ring and a reconfigurable dipole frequency selective surface. Thereupon there are shown fundamental topics like microstrip antennas, PIN diodes and the fundamental theory of reconfigurable antennas and frequency selective surfaces. There are shown the simulations and measurements of the fabricated prototypes and it is done an analysis of some parameters like the bandwidth and radiation pattern, for the antennas, and the transmission characteristics, for the frequency selective surface. Copper strips were used in place of the diodes for proof of the reconfigurability concept